2003
DOI: 10.1016/s0886-3350(02)01919-3
|View full text |Cite
|
Sign up to set email alerts
|

Repair of late Descemet's membrane detachment with perfluoropropane gas

Abstract: We report 3 cases of Descemet's membrane detachment detected 2 to 3 weeks after surgery that was treated by intracameral injection of perfluoropropane 14% (C(3)F(8)) isoexpansile mixture. We looked at the predisposing factors, the best method of treatment, and the final outcome in cases of Descemet's membrane detachment following phacoemulsification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 7 publications
0
12
0
1
Order By: Relevance
“…Localized detachments of DM are not uncommon, but tend to heal by spontaneous reattachment causing no affect on the postoperative visual outcome 4 . In contrast, as was the case with our patient, large extensive detachments (larger than 1 mm) can result in persistent corneal decompensation and significant visual impairment if surgical intervention is not undertaken 2 . Although there are case reports in the literature that describe 1 mm detachments spontaneously reattaching at any timeframe (weeks, months, years) 5…”
Section: Discussionmentioning
confidence: 49%
“…Localized detachments of DM are not uncommon, but tend to heal by spontaneous reattachment causing no affect on the postoperative visual outcome 4 . In contrast, as was the case with our patient, large extensive detachments (larger than 1 mm) can result in persistent corneal decompensation and significant visual impairment if surgical intervention is not undertaken 2 . Although there are case reports in the literature that describe 1 mm detachments spontaneously reattaching at any timeframe (weeks, months, years) 5…”
Section: Discussionmentioning
confidence: 49%
“…C 3 F 8 gas has been used in many ophthalmologic surgical operations by virtue of its expansile property: as an intravitreal fi lling following vitrectomy, as material for pneumoretinopexy in cases of premacular hemorrhage to displace the premacular hemorrhage, 14,15 in cases of rhegmatogenous retinal detachment to close the retinal hole and reattach the retina, and in cases of Descemet's membrane detachment. [16][17][18][19] The toxic effects of C 3 F 8 gas on the corneal endothelium are well documented in the literature. 1,[11][12][13] reported that the corneal endothelial damage associated with pars plana vitrectomy and total lensectomy and C 3 F 8 gas tamponade is greater than that associated with vitrectomy combined with anterior capsule preserved lensectomy and C 3 F 8 gas tamponade; however, they did not mention the concentration of the C 3 F 8 gas.…”
Section: Discussionmentioning
confidence: 99%
“…Apesar de ser um método conhecido, é citado pela primeira vez na literatura nacional. Há uma permanência maior do gás dentro da câmara anterior (sete a 14 dias) mantendo a membrana de Descemet por mais tempo colada ao estroma, contribuindo assim para a adesão definitiva (11)(12)(13) .…”
Section: Discussionunclassified